Digital library of thesis: Administration side / Chew Soo Noan - Chew , Soo Noan (2001)
Currently, the faculty promoted a plan to rethink the way graduate students present their theses. Traditionally, the theses were produced in paper fonn and storing in library. The access of student work through this method still facing a lot of problems including less timely public access to users, shelf space required for storage, no maintenance, resources are not fully used and cost of preparing theses are high. Thus, Digital Library of Theses is proposed to eliminate all the shortcomings mentioned above. Digital Library of Theses (administration side) is a web-based theses administration system for faculty that can cater about 3 years theses and other records. The system contains three majn modules or subsystem, namely theses publication, maintenance and user access and queries. There will be two administrators, super administrator and thesis administrator managing the system with the function like add and edit faculty and department, generate reports, add and edit supervisor and etcetera to support the client side of system. The entire system is based on three-tier client/server architecture. All communications of system are done using Intranet through TCP/JP protocol. With the user-friendly interfaces, Digital Library of Theses ease administrator for remote managing and system maintenance. In addition, it helps administrator to manage theses time-effectively with less manpower. The completion of this web-based digital library theses system allows lecturer and student to access it within the local area network of faculty.